The impact of the COVID-19 pandemic on vegetable farmers in Bangladesh - Alam, Mohammad Jahangir; Kabir, A. N.; Mastura, Tamanna; Kishore, Avinash; Jackson, Tamara; Begum, Ismat Ara (Informa UK Limited, 2023)
The COVID-19 pandemic not only imposed severe health risks but also raised major challenges to the economy, due to widespread and severe measures to control the spread of the disease. Food value chains were disrupted by restrictions of the movement of people and commodities, which had significant impacts on the livelihoods of smallholder farmers. The purpose of this research is to determine the impact of the COVID-19 pandemic on Bangladeshi vegetable farmers. A total of 320 vegetable farmers were selected from the North-West region of Bangladesh. Both quantitative and qualitative data were collected through a digital survey method. Analysis revealed that around 3–5% of the marketed surplus of the farms was reduced during the pandemic due to the disturbances. The majority of the farm households reported that there was a significant reduction in their family income and, as a consequence, around 38% of farm households had cut down on their food consumption during the pandemic. The farmers were found to follow different strategies to cope with the difficulties and respond to government initiatives to mitigate such impacts. Despite all the restrictions and risks, extension services were still available to help the farmers. On the basis of the findings, this study suggests the importance of collaborative participation of the relevant bodies to decrease the effects of COVID-19 on farm households by employing all available mechanisms and focusing more on identifying effective coping strategies that can be supported in the event of future shocks, for more sustainable and resilient food systems.